Genetic and nongenetic risk factors for childhood cancer - Spector, Logan G; Pankratz, Nathan; Marcotte, Erin L (The Pediatric clinics of North America, 2015)
The causes of childhood cancer have been systematically studied for decades, but apart from high-dose radiation and prior chemotherapy there are few strong external risk factors. However, inherent risk factors including birth weight, parental age, and congenital anomalies are consistently associated with most types of pediatric cancer. Recently the contribution of common genetic variation to etiology has come into focus through genome-wide association studies. These have highlighted genes not previously implicated in childhood cancers and have suggested that common variation explains a larger proportion of childhood cancers than adult. Rare variation and nonmendelian inheritance may also contribute to childhood cancer risk but have not been widely examined.